Construcción de aceras por dks ingenierìa y construcciòn S.A.S (2022)
As upcoming engineers of the Antonio Nariño University it is important to interact with the environment, beyond the classroom, this makes us develop to the maximum as professionals, for this reason it is essential to put into practice all the theory we have acquired over the years and thus provide a contribution to society in the work projects that are being carried out, specifically with the company D.K.S INGENIERÍA Y CONSTRUCCIÓN S.A.S.